Study on the Effect of Terminalia chebula Softening Treatment on Physical and Mechanical Properties of the Banana Fabric - Anitha. S (Journal of Natural Fibers)
The demand for environmentally friendly clothing and fabrics continues to increase globally. Banana fiber is a sustainable fiber known for its high tensile strength. It can be effectively blended with cotton and various synthetic fibers to develop versatile fabrics. The fiber’s abrasive texture is a major problem, making it difficult to wear and limiting its application in the apparel industry. The study focuses on the utilization of Terminalia chebula, an organic material, as a softening agent to address these concerns and maintain the environmentally friendly nature of the banana fabric. The experiment involved treating the banana fabric with different concentrations (20%, 40%, and 60%) of Terminalia chebula solution. The physical, comfort, and mechanical properties of the treated fabric are evaluated and compared to those of the untreated fabric. The results demonstrate that Terminalia chebula treated fabric has better comfort (both bending rigidity and stiffness) Notably, the treated fabric shows a substantial improvement in crease recovery and drapability. However, no effective improvement was found in tensile and seam strength. In addition, the study explores the potential of T. chebula as a multifunctional textile finish, making a valuable contribution to the growth of sustainable and eco-friendly textile finishing methods.